Teachers of Preschool and Early School Education Facing the Challenge of Working With Talented Young Learners - a Study Based on Qualitative and Quantitative Research - Aneta Kamińska (Ignatianum University Press, 2024)
Research objective: The main goal of this article is to portray the challenges that early education and preschool teachers encounter when working with talented young learners in public preschools and kindergartens. Problem and research methods: The author investigates the complexities of working with talented young learners, utilizing quantitative methods such as standardized surveys and interviews with early education and preschool teachers. The process of argumentation: The introduction outlines the topic, followed by a brief description of the challenges in teaching talented learners. The research method is then discussed. Finally, the findings and recommendations for practice are presented. Research results: The findings indicate that early education and preschool teachers face some challenges in teaching talented learners, mostly connected with recognition, diagnosis, and individualized instruction. Many teachers feel unprepared, lack sufficient time, and receive little support from colleagues and administrators. They also seldom seek help from specialists. Conclusions, innovations, and recommendations: There is a need for comprehensive political regulation in Poland to enhance the individualization of education for talented young learners. Support for teachers through collaboration with headmasters, parents, and specialists is vital. Teamwork and assistance are essential to effectively meet the needs of these learners.